Development And Characterization Of Topical Phospholipid Formulations Containing Chromolaena Odorata Extract To Ameliorate Skin Ageing - Hussein Majeed, Shakho Shahad (2022)
Skin ageing is accelerated by external factors such as UV radiation and environmental pollutants. The instability of natural antioxidants that have been used to counteract the damaging effects, along with the need to penetrate the skin to reach the affected layer, are great challenges. This study involved the preparation of four phospholipid-based topical formulations containing Chromolaena odorata (CO) extract to ameliorate the effects of skin ageing. Liposomes, transfersomes, ethosomes and lecithin organogels (LOs) were selected as they were deemed to be able to deliver the extract to the dermal layer and retain it adequately to exert anti-ageing effects. Characterization studies revealed that the smallest mean particle size of 281.77 ± 6.33 nm, was formed by the CO-loaded liposomes. The zeta potential of the formulations was in the range of -88.7 ± 8.70 to -27.07 ± 0.86 mV. The pH of the formulations was in the range of 6.8 to 7.4. Entrapment efficiency (EE) of CO-loaded liposomes and CO-loaded ethosomes was 77.12% ± 2.10 and 69.40% ± 2.29, respectively. Transmission Electron Microscopy (TEM) results showed that all vesicles were spherical in shape whilst 1H Nuclear Magnetic Resonance (1H NMR) confirmed the entrapment of extract molecules in the phospholipid bilayers. Stability studies revealed that CO-loaded ethosomes showed the longest stability, among all the formulations, at both 4 °C xix ± 2 °C and 30 °C ± 2 °C up to one year. The in vitro release study outcomes revealed that the highest percentage of the extract release was observed from CO-loaded ethosomes (68%).